Effect of Bacillus apiarius or Torulaspora delbrueckii on performance of broiler chicken - I.P Kompiang; D Zaenuddin; Supriyati . (Jurnal Ilmu Ternak dan Veteriner, 2002)
An experiment had been conducted to determine the effect of B. apiarius and T. delbrueckii, isolated from chicken gut, supplementation on the broiler performance. Evaluation was conducted by comparing performance of broiler chicken: (I) negative control/basal diet without antibiotic growth promotor (GPA), (II) positive control/basal diet with GPA, zinc-bacitracin, (III) basal diet + B. apiarius 5 ml/l in drinking water daily, (IV) basal diet + T. delbrueckii 5 ml/l in drinking water daily, (V) basal diet + B. apiarius 5 ml/l in drinking, daily during the first week, and there after given twice weekly, (VI) basal diet + T. delbrueckii 5 ml/l in drinking, daily during the first week, and there after given twice weekly and (VII) reference control, basal diet + commercial probiotic 5 ml/l in drinking, daily during the first week, and there after given twice weekly. Thirty two DOC broilers were used for each treatment, divided into 4 replicates (8 birds/replicate) and raised in wire cages for 5 weeks. Feed and water were given ad lib., body weight, FCR (feed conversion ratio) and mortality were recorded. The results showed that the performance of the birds supplemented daily (III) or twice weekly (V) with B. apiarius are similar to positive control (II) or reference control (VII) and significantly (P<0.05) better than the negative control (I). Performance of the birds supplemented daily with T. delbrueckii (IV) are similar to positive control (II) or reference control (VII) and significantly (P<0.05) better than the negative control (I). However, when given only twice weekly (VI), their bodyweight gain was significantly (P<0.05) lower than treatment II, III, IV and VII, but similar to treatment I. Its FCR value was similar to the other treatments. Mortality was low, an average of 1.3/32 birds, during the trial period and there were no differences between all treatments. It is concluded that both B. apiarius and T. delbrueckii could be utilized as probiotic candidates, replacing the GPA function. However, B. apiarius is better potential as probiotic candidate compare to T. delbrueckii. Key words: Bacillus apiarius, Torulaspora delbrueckii, probiotic, GPA, broiler